2020
DOI: 10.3390/jcs4020057
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hematite Nanodiscs from Natural Laterites and Investigating Their Adsorption Capability of Removing Ni2+ and Cd2+ Ions from Aqueous Solutions

Abstract: In this work, disc-like hematite (Fe2O3) nanoparticles were prepared using a readily available inexpensive earth material, ferruginous laterite, via a low-cost synthesis route. Prepared hematite nanoparticles were characterized using X-Ray diffraction (XRD), inductively coupled plasma mass spectroscopy (ICP-MS), particle size analyzer (PSA), Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), and nitrogen adsorption-desorption analyzer. The performance of hematite nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The adsorption process is described at the equilibrium using adsorption isotherms that quantify the amount of the substance adsorbed per unit mass of adsorbent as a function of the equilibrium concentration of the adsorbate [ 40 ]. Commonly used adsorption isotherms are the Langmuir and Freundlich isotherm models [ 41 ]. Other adsorption isotherms include Tempkin, Dubinin–Radushkevich, Flory–Huggins, Hill, and Redlich–Peterson, Toth, Radke–Prausnitz, Koble–Corrigan, Sips, Fritz–Schluender, Jovanovic, Brunauer–Emmett–Teller, MacMillan–Teller, Vieth-Sladek, Harkins–Jura, Halsey, Frenkel–Halsey–Hill, Henderson, Valenzuela-Myers, Baudu and Elovich [ 42 ].…”
Section: Biopolymer-based Dye Removal Technologiesmentioning
confidence: 99%
“…The adsorption process is described at the equilibrium using adsorption isotherms that quantify the amount of the substance adsorbed per unit mass of adsorbent as a function of the equilibrium concentration of the adsorbate [ 40 ]. Commonly used adsorption isotherms are the Langmuir and Freundlich isotherm models [ 41 ]. Other adsorption isotherms include Tempkin, Dubinin–Radushkevich, Flory–Huggins, Hill, and Redlich–Peterson, Toth, Radke–Prausnitz, Koble–Corrigan, Sips, Fritz–Schluender, Jovanovic, Brunauer–Emmett–Teller, MacMillan–Teller, Vieth-Sladek, Harkins–Jura, Halsey, Frenkel–Halsey–Hill, Henderson, Valenzuela-Myers, Baudu and Elovich [ 42 ].…”
Section: Biopolymer-based Dye Removal Technologiesmentioning
confidence: 99%
“…Among them, adsorption is mainly used, because it is highly efficient, easy to use, relatively inexpensive, and the adsorbent agents can be reused several times. 5,9–19 However, conventional adsorbent agents such as fibers, foams, and resins have low surface area, making them less active and inefficient. 5,13,16 To address these shortcomings, numerous studies have reported new adsorbent materials based on metal nanoparticles, 5,15,17,20,21 polymers, 13 modified biomolecules, 10–12 and porous materials.…”
Section: Introductionmentioning
confidence: 99%
“…5,13,16 To address these shortcomings, numerous studies have reported new adsorbent materials based on metal nanoparticles, 5,15,17,20,21 polymers, 13 modified biomolecules, 10–12 and porous materials. 9,14,22…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of economical, eco-friendly, and treatment performance, adsorption represents one of the most promising options to remove As from contaminated wastewater [6]. Adsorbents from low-cost sources such as agricultural waste [7], industrial by-products [8], and natural minerals [9,10] have been investigated for the treatment of contaminated water laden with heavy metals such as As, Cr, and Ni.…”
Section: Introductionmentioning
confidence: 99%